2014
DOI: 10.1186/s12865-014-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

An increase of CD83+ dendritic cells ex vivo correlates with increased regulatory T cells in patients with active eosinophilic granulomatosis and polyangiitis

Abstract: BackgroundEosinophilic granulomatosis with polyangiitis (EGPA) is a rare disease characterized by the presence of allergic granulomatosis and necrotizing vasculitis with eosinophilic infiltration. The etiology of EGPA is unknown. Dendritic cells (DCs) are not only critical for the induction of primary immune responses; they may also be important for the induction of immunological tolerance and the regulation of the type of T-cell-mediated immune response. To investigate whether DC maturation is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…51 In addition, we have reported that the percentage of CD83 + dendritic cells, which are mature dendritic cells, was significantly correlated with the number of naturally occurring or inducible T reg cells (CD4 + CD25 + T cells producing IL-10) or the number of TGF-β cells, but not the number of eosinophils in patients with EGPA. 52 We have also reported that the amount of CD80 + , CD27 + , or CD95 + expressed on CD19 + B cells was increased in some patients with EGPA, especially in those who experienced more frequent relapses than in those who sel- 27 In the present study, we had detected more CD4 + T cells producing IL-25 in peripheral blood in patients with EGPA at relapse than in those at remission or in patients with BA, although the difference was very small.…”
Section: Discussionmentioning
confidence: 99%
“…51 In addition, we have reported that the percentage of CD83 + dendritic cells, which are mature dendritic cells, was significantly correlated with the number of naturally occurring or inducible T reg cells (CD4 + CD25 + T cells producing IL-10) or the number of TGF-β cells, but not the number of eosinophils in patients with EGPA. 52 We have also reported that the amount of CD80 + , CD27 + , or CD95 + expressed on CD19 + B cells was increased in some patients with EGPA, especially in those who experienced more frequent relapses than in those who sel- 27 In the present study, we had detected more CD4 + T cells producing IL-25 in peripheral blood in patients with EGPA at relapse than in those at remission or in patients with BA, although the difference was very small.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the increased Tregs mediated by tolerogenic DCs suppress the antitumor response generated by effector lymphocytes. 16,45 Recently, others have reported that inhibition of p38 mitogen-activated protein kinase in DCs overcomes Treg-mediated immunosuppression and prompts antitumor immune responses. 46 These findings may help improve DC-based immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…15 Tregs function by a direct cell contact manner and produce transforming growth factor-β (TGF-β) and IL-10 and can be separated into two forms: "natural" Tregs (Foxp3+CD4+), which originate in the thymus, and "induced" Tregs (CD25+CD4+), which are derived from naive T cells in the periphery. 16 They are similar, both phenotypically and functionally, but are reported to be different in "Helio" expression, which is a zinc finger transcription factor. 17 Inducible Tregs are derived from naive T cells by costimulation with T-cell receptors and TGF-β.…”
Section: Doi: 101309/ajcpujgmvv6zf4ggmentioning
confidence: 99%
“…Except for a study of CD83 and CD208, 17 this is, to our knowledge, the first immunostaining study of lung tissue in EGPA. This is the first lung tissue transcriptome study in EGPA.…”
Section: Discussionmentioning
confidence: 96%